Strategic human resource management : text and cases - Azmi, Feza Tabassum (Cambridge : Cambridge University Press, 2019)
This book provides a comprehensive and up-to-date text in the subject. It seeks to address a wide gap existing in terms of the availability of a book that provides extensive coverage in the field. It aims to provide students in human resource management courses and practising managers with a comprehensive view of essential concepts and techniques in a highly readable and understandable form. This book particularly focuses on practical applications, examples and cases that managers can utilise in gaining insights into the subject in order to carry out their HR-related responsibilities. It focuses on practical applications, examples and cases that will be useful for both students and HR managers. It serves two important purposes: to provide an academically rigorous study, and at the same time, offer comprehensive and user-friendly pedagogy. The case studies cited in the book are from across the globe, including studies from India, and will appeal to a large audience.
Title from publisher's bibliographic system (viewed on 24 Apr 2019).
Keywords: Personnel management